Myelotoxicity as a prognostic factor in patients with advanced breast cancer treated with chemotherapy: A pooled analysis of two randomised trials conducted by the hellenic cooperative oncology group - Koutras, A.K.; Fountzilas, G.; Dafni, U.; Dimopoulos, M.A.; Pectasides, D.; Klouvas, G.; Papakostas, P.; Kosmidis, P.; Samantas, E.; Gogas, H.; Briasoulis, E.; Vourli, G.; et al. (Anticancer Research, 2008)
Background: A number of studies have shown that absence of myelotoxicity during chemotherapy is associated with worse outcome for various types of cancer, including carcinoma of the breast. The aim of this study was to determine whether myelosuppression in patients being treated with chemotherapy for advanced breast cancer has an impact on their prognosis. Patients and Methods: A retrospective review was conducted of a series of 475 patients with advanced breast cancer enrolled in two randomised trials, who received first-line chemotherapy. The impact of severe (grade 3 or 4) hematological toxicity on survival and time to disease progression was assessed. Results: When severe myelotoxicity was evaluated as a whole, a significant negative association for time to disease progression and a trend for a worse survival were demonstrated. In multivariate analysis, hematological toxicity retained its significance as an independent negative prognostic factor for time to disease progression. Conclusion: Our findings do not confirm the results of previous studies which have demonstrated a better outcome for patients experiencing hematological toxicity during treatment.
Keywords: Advanced; breast cancer; Chemotherapy; Myelotoxicity; Prognosis